Non-linear controls of soil pH and climate on radiocarbon-based turnover of soil organic carbon fractions across temperate to alpine forests - Margaux Moreno-Duborgel; Claudia Guidi; Roman Flury; Sia Gosheva-Oney; Beatriz González-Domíngez; Mirjam Brühlmann; Luisa Isabell Minich; Negar Haghipour; Katrin Meusburger; Alexander Sohrab Brunmayr; Marco Griepentrog; Samuel Abiven; et al. (Soil Biology and Biochemistry, 2026)

Inter- and intraspecific variation in foliar elemental concentrations in alpine plants - Feline Peters; Stefan Dullinger; Andrea Watzinger; Mathias Mayer; Karl Hülber; Norbert Helm; Kryštof Chytrý; Vanja Matijević; Paula Olías García; Nicolas Türk; Peter Hietz (Alpine Botany, 2026)
Plant species differ in their nutrient uptake, yet the relative importance of species identity versus environmental variables in shaping foliar elemental composition remains poorly understood. We collected foliar samples from ten alpine plant species across 21 plots spanning an elevational gradient of ~ 1000 m on the silicate-based soils of Schrankogel, Austria. Our aim was to disentangle the effects of species identity, site properties, and leaf traits on the concentrations of 16 elements. Foliar elemental concentrations showed a clear correlation structure, reflecting similarities in uptake mechanisms, physiological function, and stoichiometric requirements. Species identity was the dominant driver, explaining 41% of unique variance — far exceeding the contributions of site/soil properties or leaf traits. However, substantial interactions between species, site properties, and leaf traits indicate that element-environment relationships are species-specific, reflecting differences in uptake mechanisms or requirements among species. Soil temperature, soil carbon, and leaf age were the most important individual predictors across elements. Overall, the patterns suggest that while species identity predominantly drives alpine plant elemental composition, elements associated with mineral weathering (Fe, Al) and organic matter cycling (N, P) remain sensitive to environmental conditions, with implications for nutrient cycling under climate change in mountain ecosystems.

Prediction of nutritional impact of the mango sector in Côte d’Ivoire: past, present and future - Aurélie Bechoff; Mary Nkongho Tanyitiku; Jean-Mathias Konan Koffi; Yardjouma Silue; Ery Marilyne Christina Hien; Eric Malézieux; Emile Faye; Victoria Bancal; Claudie Dhuique-Mayer (Food Security, 2026)

Temperate Forest Floors: Ecosystem Hubs in Transition? - Friederike Lang; Jörg Prietzel; Frank Hagedorn; Klaus Kaiser; Stefanie Schulz; Mathias Mayer; Lars Vesterdal; Jürgen Bauhus; Maï Bergmann; Sebastian Bibinger; Martin I. Bidartondo; Jingxuan Olivia Chen; et al. (Global Change Biology, 2026)
The forest floor (FF) plays a key role in carbon, nutrient, and water cycling. It is the biologically most active compartment of forest soils, highly responsive to environmental conditions. Yet, its response to current changes in environmental conditions and forest management is understudied. Temperate forests are among the best studied ecosystems globally, providing the necessary ecological and biogeochemical background information to assess FF changes. Here, we focus on identifying existing knowledge and gaps in our understanding of the functioning of the FF. Interactions between FF biota and abiotic FF components show multifactorial dependencies with environmental conditions and drive FF turnover. Vice versa, the turnover of FF regulates carbon, nutrient, and water cycling. With slow litter decomposition and limited bioturbation, organic matter accumulates, nutrients cycle tightly within the FF, and water passes through this layer partly along preferential pathways. With rapid litter decomposition and intense bioturbation, FF accumulation is little, the mineral soil is the main nexus for plant nutrient uptake and organic matter transformation, and water infiltrates the mineral soil more homogeneously. The interconnectedness with the adjacent ecosystem compartments is a crucial feature of the FF, feeding back to its functioning and making it a central hub of forest processes. The FF morphology reflects these processes and therefore has untapped potential as an indicator of soil and ecosystem health. Under forest change, the FF might lose its functionality, with negative impacts on nutrient provision, water storage, and carbon sequestration. Consequences for forest growth could be strong and even detrimental. Hence, improved knowledge of FF characteristics and their linkages to mineral soils and aboveground ecosystem compartments is crucial for assessing forest resilience to progressing environmental changes.

Climate drivers of historic tree growth in the Vienna Woods and prediction of future performance of eight selected tree species - Klaus Dolschak; Emilia Winter Artusio; Mathias Mayer; Michael Grabner; Michael Tatzber; Iftekhar U. Ahmed; Elisabeth Wächter; Isolde K. Berger; Pétra Berger; Wolfgang Wanek; Torsten W. Berger (Forest Ecology and Management, 2026)

Exploring social acceptability of energy sufficiency policies - Mathias Guérineau; Julie Mayer; Pauline Pedehour; Lucie Poinet (Journal of Environmental Management, 2026)

Modelling the economy-wide effects of unilateral CO2 pricing under different revenue recycling schemes in Austria - Identifying structural model uncertainties - Mathias Kirchner; Laura Wallenko; Mark Sommer; Gabriel Bachner; Claudia Kettner; Thomas Leoni; Jakob Mayer; Nathalie Spittler; Judith Köberl; Veronika Kulmer (Energy and Climate Change, 2025)

Ranked growth response to drought for 14 tree species in a temperate forested landscape in Austria - Emilia Winter Artusio; Klaus Dolschak; Mathias Mayer; Michael Grabner; Michael Tatzber; Iftekhar U. Ahmed; Elisabeth Wächter; Isolde K. Berger; Pétra Berger; Wolfgang Wanek; Torsten W. Berger (Forest Ecology and Management, 2025)

Increased Belowground Carbon Allocation Reduces Soil Carbon Losses Under Long‐Term Warming - Andreas Schindlbacher; Steve Kwatcho Kengdo; Jakob Heinzle; Ye Tian; Mathias Mayer; Josef Gadermaier; Chupei Shi; Caro Urbina Malo; Xiaofei Liu; Erich Inselsbacher; Robert Jandl; Carlos A. Sierra; et al. (Global Change Biology, 2025)
The response of the carbon cycle in forests to global warming could lead to a positive climate feedback if warming accelerates the mineralization of soil organic carbon (SOC), thereby causing net emissions of CO 2 into the atmosphere. In Europe, carbon‐rich alpine forest soils could be particularly affected by global warming, as a greater rise in temperature is expected in this region than the global average. Here we show that nearly two decades of experimental soil warming (+4°C during the snow‐free seasons) in a mountain forest in the Northern Limestone Alps significantly (~13% per 1°C warming) and persistently (no change in response over 18 years) increased soil CO 2 effluxes. The SOC stocks in the warmed plots decreased compared to controls, yet non‐significantly, and quantitatively much less than the surplus carbon outflux from warmed soil suggests. We attribute the increase in soil CO 2 efflux primarily to stimulation of root respiration, which was most sensitive to long‐term warming. Furthermore, increased root production, faster fine root turnover, and increased root exudation likely not only facilitated autotrophic respiration but also replenished the SOC pool. The radiocarbon age of SOC indicates a rejuvenation of SOC likely by increased input of root carbon into the lower topsoil. Overall, our findings suggest that increased C allocation into the rhizosphere can at least partially compensate for the C loss through increased SOC mineralization with rising temperatures over many years.

Substantial Deep‐Soil Carbon Losses Outweigh Topsoil Gains in European Beech Forests Since the 1980s - Mathias Mayer; Klaus Dolschak; Emilia Winter Artusio; Michael Grabner; Michael Tatzber; Iftekhar U. Ahmed; Elisabeth Wächter; Selina Türtscher; Leopold Lindebner; Isolde K. Berger; Pétra Berger; Wolfgang Wanek; et al. (Global Change Biology, 2025)
Soils are a major reservoir for organic carbon (C), with subsoils (> 20–30 cm soil depth) storing most of this C. Predicting the response of deep‐soil C to global change remains a critical research priority; yet long‐term field observations for forests are scarce. In this study, we assessed decadal C dynamics in mineral soils to 90 cm depth of 62 temperate mature stands of European beech ( Fagus sylvatica ) in Austria using data from sampling campaigns in 1984, 2012, and 2022. Our results show an increase in C stocks between 0 and 20 cm and a significant decrease in C stocks at 20–50 cm and 50–90 cm soil depth, suggesting substantial C losses from deep soils. These deep soil C losses outweighed the C gain in topsoils, resulting in a soil C loss of −0.44 ± 0.19 Mg C ha −1 year −1 since the 1980s. Organic‐rich calcareous soils appeared to be particularly vulnerable to C loss, while soils containing high amounts of iron and manganese were less affected, probably because they stabilize C more effectively. We suggest that changes in regional climate (i.e., warmer and wetter) and factors such as changes in litter inputs and rooting depth may underlie the observed patterns of depth‐dependent soil C changes. The estimated soil C loss accounted for 17% of the C accumulated in aboveground biomass over the same period, as determined by dendrochronological analysis, indicating a reduction in the ecosystem's C sink capacity since the 1980s. Our results highlight the importance of including deep‐soil C storage in forest ecosystem C cycle assessments, as it plays a key role in the overall ecosystem C balance.

Meta-analysis shows global water availability thresholds for the contents of soil organic carbon and its fractions are only partly affected by nitrogen addition - Yifei Peng; Jianghuan Qin; Weixue Luo; Lu Yang; Mathias Mayer (CATENA, 2025)

Nitrogen addition reduces litter decomposition but does not affect litter production and chemistry in an alpine shrubland - Abdulazeez Abubakar; Mathias Mayer; Mathias Neumann; Qiao Gao; Dong Wang (Plant and Soil, 2025)

Variability in fine root decomposition after forest thinning: effects of harvest intensity and root size - Dong Wang; Mathias Neumann; Mathias Mayer; Douglas L. Godbold; Hangyu Lan; Xinli Chen; Qingwei Guan (European Journal of Forest Research, 2024)

A global meta-analysis of forest harvesting effects on soil respiration, its components, and temperature sensitivity - Lu Yang; Huiru Zhang; Jianghuan Qin; Xianzhao Liu; Mathias Mayer (Agricultural and Forest Meteorology, 2024)

Soil aggregate stability governs field greenhouse gas fluxes in agricultural soils - Stijn G. van den Bergh; Iris Chardon; Márcio F.A. Leite; Gerard W. Korthals; Jochen Mayer; Mathias Cougnon; Dirk Reheul; Wietse de Boer; Paul L.E. Bodelier (Soil Biology and Biochemistry, 2024)

Plant–soil interactions alter nitrogen and phosphorus dynamics in an advancing subarctic treeline - Jasmin Fetzer; Pavel Moiseev; Emmanuel Frossard; Klaus Kaiser; Mathias Mayer; Konstantin Gavazov; Frank Hagedorn (Global Change Biology, 2024)
Treelines advance due to climate warming. The impacts of this vegetation shift on plant–soil nutrient cycling are still uncertain, yet highly relevant as nutrient availability stimulates tree growth. Here, we investigated nitrogen (N) and phosphorus (P) in plant and soil pools along two tundra–forest transects on Kola Peninsula, Russia, with a documented elevation shift of birch‐dominated treeline by 70 m during the last 50 years. Results show that although total N and P stocks in the soil–plant system did not change with elevation, their distribution was significantly altered. With the transition from high‐elevation tundra to low‐elevation forest, P stocks in stones decreased, possibly reflecting enhanced weathering. In contrast, N and P stocks in plant biomass approximately tripled and available P and N in the soil increased fivefold toward the forest. This was paralleled by decreasing carbon (C)‐to‐nutrient ratios in foliage and litter, smaller C:N:P ratios in microbial biomass, and lower enzymatic activities related to N and P acquisition in forest soils. An incubation experiment further demonstrated manifold higher N and P net mineralization rates in litter and soil in forest compared to tundra, likely due to smaller C:N:P ratios in decomposing organic matter. Overall, our results show that forest expansion increases the mobilization of available nutrients through enhanced weathering and positive plant–soil feedback, with nutrient‐rich forest litter releasing greater amounts of N and P upon decomposition. While the low N and P availability in tundra may retard treeline advances, its improvement toward the forest likely promotes tree growth and forest development.

A global synthesis and conceptualization of the magnitude and duration of soil carbon losses in response to forest disturbances - Mathias Mayer; Andri Baltensweiler; Jason James; Andreas Rigling; Frank Hagedorn (Global Ecology and Biogeography, 2024)
Aim Forest disturbances are increasing around the globe due to changes in climate and management, deteriorating forests' carbon sink strength. Estimates of global forest carbon budgets account for losses of plant biomass but often neglect the effects of disturbances on soil organic carbon (SOC). Here, we aimed to quantify and conceptualize SOC losses in response to different disturbance agents on a global scale. Location Global. Time Period 1983–2022. Major Taxa Studied Forest soils. Methods We conducted a comprehensive global analysis of the effects of harvesting, wildfires, windstorms and insect infestations on forest SOC stocks in the surface organic layer and top mineral soil, synthesizing 927 paired observations from 151 existing field studies worldwide. We further used global mapping to assess potential SOC losses upon disturbance. Results We found that both natural and anthropogenic forest disturbances can cause large SOC losses up to 60 Mg ha −1 . On average, the largest SOC losses were found after wildfires, followed by disturbances from windstorms, harvests and insects. However, initial carbon stock size, rather than disturbance agent, had the strongest influence on the magnitude of SOC losses. SOC losses were greatest in cold‐climate forests (boreal and mountainous regions) with large accumulations of organic matter on or near the soil surface. Negative effects are present for at least four decades post‐disturbance. In contrast, forests with small initial SOC stocks experienced quantitatively lower carbon losses, and their stocks returned to pre‐disturbance levels more quickly. Main Conclusions Our results indicate that the more carbon is stored in the forest's organic layers and top mineral soils, the more carbon will be lost after disturbance. Robust estimates of forest carbon budgets must therefore consider disturbance‐induced SOC losses, which strongly depend on site‐specific stocks. Particularly in cold‐climate forests, these disturbance‐related losses may challenge forest management efforts to sequester CO 2 .

Estimating the response of Himalayan old-growth mountain forests to decreased monsoon precipitation - Norbu Wangdi; Iftekhar Uddin Ahmed; Mathias Mayer; Mani Prasad Nirola; Karma Orong; Norbu Zangmo; Douglas L. Godbold; Georg Gratzer; Andreas Schindlbacher (Agricultural and Forest Meteorology, 2023)

Elevation dependent response of soil organic carbon stocks to forest windthrow - Mathias Mayer; Silvan Rusch; Markus Didion; Andri Baltensweiler; Lorenz Walthert; Fabienne Ranft; Andreas Rigling; Stephan Zimmermann; Frank Hagedorn (Science of The Total Environment, 2023)

Specific root respiration of three plant species as influenced by storage time and conditions - Zana A. Lak; Hans Sandén; Mathias Mayer; Boris Rewald (Plant and Soil, 2020)
Aims Specific root respiration (RR S ) is a key root trait, determining i.e. nutrient foraging and uptake efficiencies. However, a considerable uncertainty exists regarding the effects of storage time and conditions on RR S measurements. Methods Fine root CO 2 efflux rates of three plant types (tree seedling Carpinus betulus , legume Pisum sativum , grass Lolium perenne ) were measured as depending on storage time (30–1440 min post-rinsing) and conditions (i.e. attached to plant, warm and cold water storage, and storage under dry conditions). Results Short-term storage conditions (30 min) had a significant effect on measured RR S rates, in specific, RR S rates of all three species were significantly lower under dry storage. Irrespective of plant species or temperature, storage of excised roots in water did not affect RR S for 300 min,. RR S measurements remained stable for 1 day if roots were stored cold. Conclusions Our results have important implications on measurement routines of RR S —a generally understudied root trait. Henceforth it seems reasonable to collect roots in the field and transport them, hydrated but even uncooled, to the laboratory for subsequent measurements for at least 300 min post-rinsing.

Herbivory modulates soil CO2 fluxes after windthrow: a case study in temperate mountain forests - Mathias Mayer; David Keßler; Klaus Katzensteiner (European Journal of Forest Research, 2020)
Ungulate herbivory can alter functional plant communities of early-successional forest ecosystems. The consequences of such vegetation changes on soil carbon cycling are still not fully understood. Here, we used an ungulate exclusion experiment to investigate how different levels of herbivory and associated changes in vegetation succession modulate soil CO 2 efflux and its heterotrophic and autotrophic sources following windthrow in temperate mountain forests. Our results indicate that only high levels of ungulate herbivory and associated vegetation shifts from tree to rather grass dominated plant communities affect soil CO 2 fluxes. We did not find evidence that a moderate herbivory level and accompanied smaller shifts in the functional plant community affect soil CO 2 fluxes. A greater soil CO 2 efflux under the influence of high herbivory pressure was primarily attributed to accelerated heterotrophic respiration, likely due to warmer soil conditions. Moreover, autotrophic respiration from grass roots and associated microbial communities is suggested to contribute to higher soil CO 2 fluxes. We conclude that intense herbivory and accompanied successional changes in the functional plant community enhance soil carbon losses following forest windthrow. This might have negative consequences for the soil carbon stocks and for the climate system.

Moth Outbreaks Reduce Decomposition in Subarctic Forest Soils - Hans Sandén; Mathias Mayer; Sari Stark; Taru Sandén; Lars Ola Nilsson; Jane Uhd Jepsen; Piippa Riitta Wäli; Boris Rewald (Ecosystems, 2020)

Gefüge und Eigenschaften einer mehrphasigen intermetallischen Titanaluminidlegierung für innovative Leichtbauanwendungen - Andrea Gaitzenauer; Mathias Schenk; Wolfgang Kuchling; Helmut Clemens; Patrick Voigt; Robert Hempel; Svea Mayer (BHM Berg- und Hüttenmännische Monatshefte, 2013)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)